1999
DOI: 10.1111/j.1572-0241.1999.01278.x
|View full text |Cite
|
Sign up to set email alerts
|

The Clinicopathological Significance of P21 and P53 Expression in Esophageal Squamous Cell Carcinoma: An Analysis of 153 Patients

Abstract: Thus, p21 and p53 had prognostic value for esophageal squamous cell carcinomas. Loss of p21 expression was shown without p53 alternations, indicating that other mechanisms are also involved in turning off the gene. The pattern of p21 and p53 expression predicts an aggressive clinical course of esophageal squamous cell carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 37 publications
4
25
0
Order By: Relevance
“…48,49) Down-regulation of p73 expression decreases the induction of apoptosis and cell cycle arrest through down-regulation of p21 function, 19,20) which may cause cancer cells to become more malignant. 50,51) But, as shown in Table 2, p73 expression was not correlated with various clinicopathological factors relating to esophageal cancer progression or the patient's outcome. This is the first report on p73 expression in esophageal cancers and further studies will be necessary to reach a conclusion concerning the mechanism of down-regulation of p73 expression and the clinicopathological role of p73 expression in esophageal cancers.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…48,49) Down-regulation of p73 expression decreases the induction of apoptosis and cell cycle arrest through down-regulation of p21 function, 19,20) which may cause cancer cells to become more malignant. 50,51) But, as shown in Table 2, p73 expression was not correlated with various clinicopathological factors relating to esophageal cancer progression or the patient's outcome. This is the first report on p73 expression in esophageal cancers and further studies will be necessary to reach a conclusion concerning the mechanism of down-regulation of p73 expression and the clinicopathological role of p73 expression in esophageal cancers.…”
Section: Discussionmentioning
confidence: 98%
“…In esophageal squamous cell carcinoma, several reports have proposed that no correlation exists between the p53 mutation and loss of p21 expression. [50][51][52] Therefore, another route for the activation of p21 WAF1 independent of the p53 pathway has been suggested. 53) On the other hand, p73 expression has been found to be strongly correlated with p21 expression in recent studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed the prognostic significance of p21 expression in patients with esophageal squamous cell carcinoma (11)(12)(13). p21 waf1 overexpression has been reported to be associated with a worse prognosis in bladder (14), ovarian (15), breast (16) and esophageal carcinomas (17,18), and also in oral SCC (19).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated reduced expression of p21 as an indicator of poor esophageal cancer prognosis [175,176], while others have found no significant correlation [173,177]. Conversly others have claimed that p21 overexpression is correlated with a poorer prognosis [165,178].…”
Section: P21/waf1mentioning
confidence: 99%